Menachem Kaiser’s Quest for Family Heirloom and the Aftermath of Historical Trauma - Basiuk, Tomasz (Porównania, 2023)
Menachem Kaiser’s Plunder: A Memoir of Family Property and Nazi Treasure (2021) critiques the generic limitations of the “3G” (third-generation) memoir by pointing to its frequently sentimental tenor and facile epiphanies, perpetuated by the publishing market. Plunder focuses instead on material traces of the past and on Kaiser’s effort to reclaim property left behind by his relatives in Poland. This approach allows Kaiser to address the aftermath of historical trauma without vicariously identifying with Holocaust victims or survivors.